Efficacy of methimazole before the administration of radioactive iodine in the management of Graves’ disease: a systematic review and meta-analysis - Rufai, Ikeoluwapo Kendra Bolakale; Abioro, Imodoye; Ngene, Samuel Osobuchi; Woldeamanuel, Yohannes (São Paulo Medical Journal, 2023)
BACKGROUND: The efficacy of anti-thyroid drugs in conjunction with radioactive iodine therapy in the management of Graves’ disease is still controversial. OBJECTIVE: To compare the efficacy of pretreatment with methimazole before the administration of radioactive iodine for the treatment of Graves’ disease. DESIGN AND SETTING: A systematic review and meta-analysis was conducted at a teaching/tertiary hospital in Ibadan, Nigeria. METHODS: A systematic search of the PubMed, Embase, Cochrane Library, and Web of Science databases was performed from inception to December, 2021. RESULTS: Five studies with 297 participants were included. There was no difference in the risk of persistent hyperthyroidism when radioactive iodine was used in conjunction with methimazole compared with when radioactive iodine was used alone (relative risk: 1.02, 95% confidence interval, CI: 0.62–1.66; P = 0.95, I2 = 0%). Subgroup analysis based on the duration between discontinuation of methimazole and the administration of radioactive iodine showed a lower risk of persistent hyperthyroidism when methimazole was discontinued within 7 days before radioactive iodine use, although this did not reach statistical significance (risk ratio: 0.85, CI: 0.28–2.58). CONCLUSIONS: The use of methimazole before radioactive iodine administration was not associated with an increased risk of persistent hyperthyroidism. Concerns about medication toxicity and adverse effects should be considered when clinicians make decisions on combination therapies for the treatment of Graves’ disease. PROSPERO REGISTRATION: CRD42020150013, https://www.crd.york.ac.uk/prospero/display_record. php?RecordID=150013.